Experimental study on seismic vibration control of stockers in wafer and LCD panel fabs. (June 2021) - Chen, Yung-Tsang; Lee, Chien-Liang; Wang, Miao-Chi; Wang, Yen-Po
Abstract: Automated stocker system is widely used in semiconductor and liquid crystal display (LCD) industries for handling and storage of valuable wafers or glass panels. Massive front opening unified pods (foups) containing wafers, or cassettes storing glass panels, are placed in shelf stockers during manufacturing. Although several preventative measures have been taken, during the past earthquakes, substantial financial loss from the industries were reported, and one of the main causes was attributed to collision of the foups or cassettes and shake off from the shelfs. This paper proposes a methodology of incorporating viscous fluid dampers into the stokers to mitigate their seismic response. Unlike conventionally been done in buildings where dampers are placed between adjacent stories, it is proposed to install dampers in between the ceiling and top of the stocker. Such configuration utilizes the large velocity at the stocker top under vibration, resulting in smaller damper size, and enables a leverage mechanism that requires smaller damper force to resist the stocker's vibration. Both shake table tests and simulation of a full-scale stocker under realistic earthquakes have been conducted. Results indicate that both displacement and acceleration responses of the stocker can be significantly reduced, and dynamic response of the stocker under seismic excitations can be well predicted.